Hubungan Pengetahuan dengan Tindakan Personal Hygiene Saat Menstruasi pada Remaja di SMPN 1 Gegerbitung Wilayah Kerja Uptd Puskesmas Gegerbitung - Dini Rafisa Azahra; Susilawati Susilawati; Nunung Liawati (Malahayati Nursing Journal, 2026)
ABSTRACT Maintaining personal hygiene during menstruation is vital for adolescents’ reproductive health. It is believed that adequate knowledge influences adolescents’ personal hygiene practices during menstruation. To determine the relationship between knowledge and personal hygiene practices during menstruation among adolescents. A correlational study using a cross-sectional approach. The study population consisted of a sample of female adolescents in Years 8 and 9 at SMPN 1 Gegerbitung, within the catchment area of the Gegerbitung Community Health Centre (Puskesmas) and the Gegerbitung Community Health Centre Operational Unit (UPTD), with a sample size of 128 respondents selected using proportional random sampling. Data were collected using a knowledge questionnaire (Guttman scale) and a personal hygiene practices questionnaire (Likert scale). Data analysis was conducted using univariate and bivariate analyses with the Chi-Square test. The results showed that of the 128 respondents with good knowledge, 51 respondents (58.6%) had personal hygiene practices in the ‘good’ category. The statistical test using the Chi-Square test yielded a p-value of 0.000 (p 0.05). There is a relationship between knowledge and personal hygiene practices during menstruation among adolescents at SMPN 1 Gegerbitung within the working area of the Gegerbitung Public Health Centre (UPTD Puskesmas). Keywords: Knowledge, Personal Hygiene Actions, Menstruation, Teenager.  ABSTRAK Menjaga personal hygiene saat menstruasi sangat penting untuk kesehatan reproduksi remaja. Pengetahuan yang cukup diyakini memengaruhi tindakan personal hygiene remaja selama menstruasi. Untuk mengetahui hubungan pengetahuan dengan tindakan personal hygiene saat menstruasi pada remaja. Penelitian korelasional dengan pendekatan cross sectional. Populasi yang diteliti terdiri dari sebagian remaja putri kelas VIII dan IX di SMPN 1 Gegerbitung wilayah kerja Puskesmas Gegerbitung wilayah kerja UPTD Puskesmas Gegerbitung dengan jumlah sampel 128 responden yang diambil melalui teknik proposional random sampling. Data dikumpulkan menggunakan kuesioner pengetahuan (skala Guttman) dan kuesioner tindakan personal hygiene (skala likert).  Analisis data dilakukan secara univariat dan bivariat menggunakan uji Chi-Square. Hasil menunjukan bahwa dari 128 responden yang berpengetahuan baik yaitu sebanyak 51 responden (58,6%) tindakan personal hygiene dalam kategori baik. Hasil uji statistik menggunakan Chi-Square diperoleh nilai p-value = 0,000 (p 0,05).  Terdapat hubungan pengetahuan dengan tindakan personal hygiene saat menstruasi pada remaja di SMPN 1 Gegerbitung wilayah kerja UPTD Puskesmas Gegerbitung. Kata Kunci: Menstruasi, Pengetahuan, Personal hygiene, Remaja, Tindakan.